Peningkatan Kapasitas Guru Sekolah Dasar melalui Pendampingan Teknologi Digital untuk Pembelajaran Berkelanjutan berbasis SDGs - Arita Marini; Arifin Maksum; Juhana Sakmal; Siti Keysa Ikrimah; Dilla Aulia Ramadhani; Aurah Jauhara Ali; Cindy Suryadi; Leola Dewiyani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The urgency of mentoring teachers at Al Ashriyyah Nurul Iman Islamic Boarding School Elementary School, Parung, Bogor in utilizing digital technology for SDGs-based sustainable learning stems from the limited capacity of elementary school teachers to effectively, meaningfully, and sustainably integrate digital technology into the teaching and learning process. Rapid technological advancements have not been fully accompanied by the development of teachers’ digital pedagogical competencies, resulting in technology utilization that tends to be administrative rather than supportive of inclusive, participatory, and contextual learning related to sustainable development issues. Therefore, systematic and continuous mentoring is essential to ensure that digital learning transformation not only improves the quality of education but also contributes significantly to achieving the Sustainable Development Goals (SDGs), particularly SDG 4 on Quality Education at the elementary school level. Keywords: Elementary school teachers; digital technology; SDGs; digital literacy; collaboration